PEMBERDAYAAN MASYARAKAT BERBASIS AGROFORESTRI (HUTAN LAHAN) DALAM PENINGKATAN HASIL USAHA TANI DI DESA SASAHAN KECAMATAN WARINGINKURUNG KABUPATEN SERANG BANTEN - Hayati, Fatihah Nurul; Naim, Mochamad; Ganiadi, Mochamad (Universitas Mataram, 2024)
Indonesia's advantages in carrying out agriculture are both economic and basic needs of life. In Indonesia itself, it has been proven that there will be 40.64 million workers in the agricultural, forestry and fisheries sectors in 2023. This research aims to describe (1) the community empowerment carried out by Sasahan village through an agroforestry-based program (2) the results of farming activities from the agroforestry-based community empowerment program for the Sasahan village community. The approach used is a qualitative approach using descriptive methods. The data collection techniques used are observation, interviews and documentation. The research results show that (1) Community Empowerment carried out by Sasahan Village through the Agroforestry Based Program in Sasahan Village is that the agroforestry farming system can be used to optimize agricultural fields while preserving nature. The agroforestry program is important to implement in the Sasahan Village area. (2) Farming results from the Agroforestry-Based Community Empowerment Program for the Sasahan Village Community, the economic dimension has increased, and are categorized as sustainable. Sasahan Village is willing to implement agroforestry, and is categorized as sustainable, from the aspects of production, distribution and consumption being the main factors for economic improvement.